ACCULTURATION AS ADAKWAH MODEL OF SUNAN KALIJAGAIN PORTRAITOFISLAM NUSANTARA - Mubasyaroh Mubasyaroh (TASÂMUH, 2017)
Islam is a religion rahmatan lil ‘alamin, meaning that Islam gives mercy to all the worlds. Islam in Indonesia is unique among all other countries in the world. Islam in Indonesia is unique among all other countries in the world, because it has different characteristics with Islam that exist in other countries, to uphold the tradition. A Moslem phenomenon is a reflection of the culture of this nation. Even the colors of Islam in each race also has a unique, that Islam became a local here. This is evident in their daily lives that involve sharia law into everyday life. Even in more detail each area has a variety of unique diversity, so it appears the Islamic Java (Javanese Islam), Islam Sasak and so forth. It shows the diversity of Islam Nusantara. In the context of contact between Islam to Indonesia, the country with the followers of Islam in the world, the historical records that the influx through a channel Islamization particularly through cultural channels. Of the territory, which is interesting to study is the disseminator of Islam in Java as Walisongo (Wali Sembilan), one guardian is Sunan Kalijaga with media preaching is through arts and acculturation.